Effect Branch Pruning To Establishment On Shoot Growth and Flower Stimulation On Guava - Nafisah, Dio; Supanjani, Supanjani; Suprijono, Eko (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
GuavaCrystalsarefromTaiwan,released byministryofAgricultureDecreeNo.540/Kpts/SR.120/9/2007.GuavaCrystalvarietiesare very prospective forcommercial developmentbecauseitcanproduce throughtheyearandhasahighvitaminCcontent. Increasingpublicawarenessoftheimportanceofconsumingfreshfruitforhealthincrease the market demandforfreshfruit.Butthe highdemandforfreshguavafruitisnotsupported bytheproduction offreshfruiteveryyear.Continueddecliningguavaproductionrequires theimprovementofcultivationtechniquessothat thequalityandquantityofguavafruit increases. ThisneedstoImprove ofcultivationtechniquesformeetthe needsoffreshguava. One ofsimplestcultivationtechniquestoimprovethe yieldofCrystalguavaispruning. This research intendtodetermine the effectofcroplengthonthe growthoflateralshootsandthe flowering of Crystal guava.ThisresearchwasconductedinDecember2016untilMarch2017at guavaplantation locatedinBentiringSub-ProvinceofBengkuluProvince.ResearchusedRAKLwithone singlefactor.The factorislengthofpruning,whichcomprisedoffourlevels10cm,20cm,30 cm,40cmandcontrol.The resultsofthisstudyindicatedthatthe numberofshootsmost grownonbrancheswith 40cmlongtrimmingof 2.87shoots.Mostflowersaregeneratedon brancheswithcuttinglengthsof30cm,40cm andnottrimmed.Butbrancheswith30cm long cutsexperiencedthe mostnumberoffallenfruitswitha95% percentage ofunshelled branches.Themostfruit isproducedonbranchesthatarenotprunedthatisasmuchas8.7 will fruit.Keyword:Guava Crystals, Long Prune, Lateral Shoots, Flowering